2001
DOI: 10.1042/bj3550215
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant soluble betaglycan is a potent and isoform-selective transforming growth factor-β neutralizing agent

Abstract: Betaglycan is an accessory receptor of members of the transforming growth factor-β (TGF-β) superfamily, which regulates their actions through ligand-dependent interactions with type II receptors. A natural soluble form of betaglycan is found in serum and extracellular matrices. Soluble betaglycan, prepared as a recombinant protein using the baculoviral expression system, inhibits the actions of TGF-β. Because of its potential use as an anti-TGF-β therapeutic agent, we have purified and characterized baculovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 41 publications
3
67
0
Order By: Relevance
“…This cell line produces active TGFb 1 and TGFb 2 , and is resistant to TGFb's growth inhibitory activity (Chen et al, , 2001). The sRIII has been shown to act as a TGFb antagonist (Lopez-Casillas et al, 1994;Vilchis-Landeros et al, 2001). Consequently, the expression of a sRIII in the MDA-MB-231 cells resulted in the sequestration of the active TGFbs and antagonization of their biological activity (Bandyopadhyay et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This cell line produces active TGFb 1 and TGFb 2 , and is resistant to TGFb's growth inhibitory activity (Chen et al, , 2001). The sRIII has been shown to act as a TGFb antagonist (Lopez-Casillas et al, 1994;Vilchis-Landeros et al, 2001). Consequently, the expression of a sRIII in the MDA-MB-231 cells resulted in the sequestration of the active TGFbs and antagonization of their biological activity (Bandyopadhyay et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Baculoviral recombinant soluble betaglycan was purified as described before (22). Amounts of soluble betaglycan sBG-90 were determined by Western blot.…”
Section: Methodsmentioning
confidence: 99%
“…As a reference for comparison, we also tested the baculoviral recombinant soluble betaglycan (Fig. 8B), which binds TGF-␤ similar to the wild type membrane receptor (22). Binding of 125 I-TGF-␤2 to sBG-90 (Fig.…”
Section: Overexpression Of Mt1-or Mt3-mmps Augments the Shedding Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is a membrane bound proteoglycan that is expressed in most cell types and tissues, and has been shown to generate, upon ectodomain shedding, a soluble form of the receptor (Andres et al, 1989;Lopez-Casillas et al, 1991). While the membrane receptor enhances the TGFb e ects, the soluble form is a potent TGFb neutralizing agent (Esparza-Lopez et al, 2001;Vilchis-Landeros et al, 2001). In our previous studies, we have shown that expression of the extracellular domain of RIII in its soluble form (sRIII) in human breast cancer MDA-MB-231 cells can sequester endogenous TGFb isoforms and antagonize their activity.…”
Section: Introductionmentioning
confidence: 99%